Зміна електронної структури та зарядового стану атомів кубічного ТаС0,75 і ромбоедричного Та4С3 карбідів при заміщенні атомів вуглецю азотом - Синельниченко, О.К.; Ізвєков, А.В.; Хижун, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
The X-ray emission spectroscopy (XES) and X-ray photoelectron spectroscopy (XPS) methods are employed to study the electronic structure and charge states of atoms of a series of substoichiometric cubic TaCxN0.75–x and rhombohedral ζ-Ta4C3 and ζ-TaC0.59N0.15 compounds. For the above tantalum carbonitrides, the XES bands reflecting the energy distribution of the Ta5d-, C2p-, and N2p-like states are derived and compared on a common energy scale, and the XPS core-level binding energies are measured. A strong hybridization of Ta5d-like and C(N)2p-like states is characteristic of all the compounds under study. The present XES and XPS data reveal that, when substituting carbon atoms for nitrogen atoms in cubic TaC0.75 and rhombohedral Ta4C3 carbides, the contribution of the covalent component of the chemical bonding decreases, while those of the metallic and ionic components increase.